Some Bilinear Hardy–Steklov Type Integral Inequalities. (4th June 2021) - Benaissa, Bouharket
Abstract: The aim of this study is to give some new bilinear Hardy–Steklov type integral inequalities with functions of two variables by using the operator S T defined by (1.4).